Analysis of the Needs of Geometry Student Worksheets Based on Augmented Reality Integrated with Ethnomathematics in Elementary Schools - Dina Fitriani; Atika Sahriyanti; Fadlun Nisa’a; Ulwiyatul Pikriya Sukmawati; Ainul Fitri Ashari; Nurul Rahmawati (Sains Global Institut, Indonesia, 2026)
This study aims to analyze the learning needs for developing student worksheets integrated with local cultural context to support geometry learning in Grade V elementary school. The research employed a qualitative descriptive approach as part of the needs analysis stage in a research and development framework. The study was conducted at UPT SD Inpres Kampus IKIP, involving one Grade V teacher as the key informant and fifteen Grade V students as respondents. Data were collected through classroom observation, structured interviews, and student questionnaires. Data analysis was carried out using qualitative techniques including data reduction, data display, and conclusion verification, supported by descriptive percentage analysis of questionnaire results. The findings revealed that students experienced high difficulties in visualizing three-dimensional objects independently (82%) and perceived the current learning media as less engaging (75%). Students also showed very high interest in learning through digital technology (95%) and high interest in integrating geometry learning with local cultural contexts (88%). These results indicate an urgent need for innovative, interactive, and contextual learning materials to enhance students’ spatial understanding and engagement in geometry learning